Impact of silver nanoparticles on the nutritional properties of spirulina platensis - Liang, Sharolynne Xiao Tong (2023)
Spirulina platensis (S. plateneis) is farmed worldwide due to its nutrient-rich properties and provides multiple benefits to human health. However, the wide usage of silver nanoparticles (Ag NPs) causes pollution which may affect the nutritional quality of S. platensis. Hence, this study aimed to investigate the interaction and accumulation of Ag NPs on S. platensis, and determine the changes in biomass and nutritional value of S. platensis due to the exposure to Ag NPs. The cellular interaction and accumulation of Ag NPs on S. platensis were examined through Fourier transformed infrared (FTIR) spectroscopy and scanning electron microscope (SEM). The loss in biomass together with the macromolecules, pigments, and phenolic compounds of S. platensis was investigated upon treating with various concentrations of Ag NPs (5, 10, 25, 50 and 100 µg/mL) for 24, 48 72 and 96 h. The EDX analysis confirmed the surface accumulation of Ag NPs on Spirulina cells, while SEM images evidenced the surface alterations and damage of the treated cells. The functional groups such as hydroxyl, amine, methyl, amide I, amide II, carboxyl, carbonyl, and phosphate groups from the cell wall of the S. platensis were identified to be possibly involved in the interaction of Ag NPs with S. platensis. The results showed that the treatment of S. platensis with Ag NPs iv caused a dose and time-dependent reduction in biomass, macronutrients, pigments and phenolic compounds. The highest detrimental effects were found at 96 h with the reported values of 65.71 ± 2.79, 67.21 ± 3.98, 48.99 ± 4.39 and 59.62 ± 3.96% reduction in biomass, proteins, carbohydrates and lipids, respectively, along with 82.99 ± 7.81, 67.55 ± 2.63, 75.03 ± 1.55, and 63.43 ± 2.89% loss in chlorophyll-a, carotenoids, C-phycocyanin, and total phenolic compounds of S. platensis for 100 µg/mL of Ag NPs. Hence, the study confirmed that the exposure of Ag NPs is detrimental to S. platensis where the interaction and accumulation of Ag NPs on S. platensis caused reduction in biomass, macromolecules, pigments, and total phenolic compounds